NGHIÊN CỨU QUY TRÌNH TỔNG HỢP γ-POLYOXYMETYLEN - Bùi, Thị Hồng Phương; Vương, Văn Trường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A STUDY OF THE PREPARATION OF γ-POLYOXYMETHYLENEThis paper presents the results of preparation of γ-polyoxymethylene (γ-POM) of formaldehyde , which will be used as a components of missile propellants. The average molecular weight of the resulted product γ-POM is 3325 carbon units. The structure of the product is confirmed and its quality complies with the Russian standard TY-84-841-79.